Heritability of Regional Brain Volumes in Large-Scale Neuroimaging and Genetic Studies. (12th July 2018) - Zhao, Bingxin; Ibrahim, Joseph G; Li, Yun; Li, Tengfei; Wang, Yue; Shan, Yue; Zhu, Ziliang; Zhou, Fan; Zhang, Jingwen; Huang, Chao; Liao, Huiling; Yang, Liuqing; et al.
Abstract: Brain genetics is an active research area. The degree to which genetic variants impact variations in brain structure and function remains largely unknown. We examined the heritability of regional brain volumes ( P 100) captured by single-nucleotide polymorphisms (SNPs) in UK Biobank ( n 9000). We found that regional brain volumes are highly heritable in this study population and common genetic variants can explain up to 80% of their variabilities (median heritability 34.8%). We observed omnigenic impact across the genome and examined the enrichment of SNPs in active chromatin regions. Principal components derived from regional volume data are also highly heritable, but the amount of variance in brain volume explained by the component did not seem to be related to its heritability. Heritability estimates vary substantially across large-scale functional networks, exhibit a symmetric pattern across left and right hemispheres, and are consistent in females and males (correlation = 0.638). We repeated the main analysis in Alzheimer's Disease Neuroimaging Initiative ( n 1100), Philadelphia Neurodevelopmental Cohort ( n 600), and Pediatric Imaging, Neurocognition, and Genetics ( n 500) datasets, which demonstrated that more stable estimates can be obtained from the UK Biobank.